Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1167/tvst.9.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Mouse Choroidal and Retinal Vasculature Using Fluorescent Tomato Lectin Perfusion

Abstract: Purpose: To develop a reliable and simplified method to assess choroid and retinal vasculature on whole mount and cross sections in mice using tomato lectin (TL; Lycopersicon esculentum). Methods: Albino mice (n = 27) received 1 mg/mL of TL (conjugated to Dylight-594) intravascularly through the tail vein, jugular vein, or cardiac left ventricle. Whole mounts of the retina and choroid were evaluated using fluorescence microscopy. Perfusion with GSL-IB4 conjugated to Dylight-594 and fluorescein isothiocyanate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…Lectins are natural ligands for sugars in biological systems. Different lectins have specificity towards different glycans and have been widely used as molecular probes for detecting glycosylation in cells and, to a less extent, in animal tissues [30–31] . In this study, using fluorescently‐labelled lectins, we successfully probed the glycosylation status in human and mouse bladder cancer tissues, thus confirming the preliminary results obtained in cell line experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Lectins are natural ligands for sugars in biological systems. Different lectins have specificity towards different glycans and have been widely used as molecular probes for detecting glycosylation in cells and, to a less extent, in animal tissues [30–31] . In this study, using fluorescently‐labelled lectins, we successfully probed the glycosylation status in human and mouse bladder cancer tissues, thus confirming the preliminary results obtained in cell line experiments.…”
Section: Discussionsupporting
confidence: 81%
“…The evidence that WGA efficacy in labeling blood vessels varies depending on the labeling method (histology on free-floating sections vs. direct labeling of the vasculature during terminal transcardial perfusion) points out that the labeling efficacy of the LEA and IB4 lectins may improve upon direct injection in the bloodstream. However, a previous study where perfusion with the LEA lectin was found to be superior to IB4 to label choroidal and retinal vasculature [ 52 ] suggests that an improved method for lectin delivery may not alter the intrinsic difference of the two lectins in labeling blood vessels that we reported in our study. An independent experiment confirmed that the labeling efficacy of intracardial perfusion with the WGA lectin at a 50 µg/mL concentration and the LEA lectin histological staining in labeling blood vessels in most of the other organs analyzed (dura, spinal cord, heart, kidney, muscle) is similar.…”
Section: Discussioncontrasting
confidence: 53%
“…Other possibilities to explain the central location of cell death loss abound but depend on the details of retinal and choroidal flow of blood in the mouse, and these may be strain specific. 59 The transition zone as a possible model of GA lesions: The damage in the transition zone (with extremes in shapes, sizes, and patterns of RPE cells) resembles some of the RPE cells surrounding GA lesions in AMD. 60 – 62 The barren patch that is central–posterior in the mouse in some ways resembles the denuded patches of GA lesions in AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Other possibilities to explain the central location of cell death loss abound but depend on the details of retinal and choroidal flow of blood in the mouse, and these may be strain specific. 59 …”
Section: Discussionmentioning
confidence: 99%